Assessing the influence of geomechanical properties on the stability of weathered sedimentary rock slope - Muhamad Zahir, Muhammad Irfan; Albar, Aniza; Mohd Nordin, Mohd Mustaqim (Faculty of Civil Engineering, 2025)
Devastating incidents of rock slope failures have led to numerous fatalities, injuries, property damage, and structural failures. A detailed examination of the risks and hazards associated with rock slopes should be conducted to prevent such incidents from occurring. The purpose of this study is to evaluate the slope stability of interbedded sedimentary rock slopes for Slope Mass Rating (SMR) and Q-Slope classification using scan line surveys and photogrammetry techniques. In this work, the stability of the rock slope is classified, its kinematic properties are assessed, and a 3D model is displayed using the Slope Mass Rating (SMR) and QSlope methods. Furthermore, the weathering grade of sedimentary rock has been successfully correlated with its strength, stability, and durability. Weathering grade II rock was found in zones Alpha and Beta, whereas weathering grade III rock was found in zone Theta. The higher mechanical strength and weathering resistance values in zones Alpha and Beta correspond to their weathering grade. On the other hand, zone Theta's grade III sedimentary rock, which is classified as moderately weathered, exhibits the lowest strength and weathering resistance. Agisoft Metashape and Stereonet 11 are two tools that significantly enhance the accuracy and reliability of the data collected. Zone Alpha is expected to be stable, according to SMR and Q-slope data, while Zones Beta and Theta are predicted to have wedge failure and planar failure, respectively. The application of bolting, shotcrete, adequate drainage systems, and ongoing monitoring on the rock slopes, which have different grades of weathering and structural weaknesses, thus necessitates strict procedures to improve the safety and stability of the rock slope.